Welt-Zeit: christliche Weltchronistik aus zwei Jahrtausenden in Beständen der Thüringer Universitäts- und Landesbibliothek Jena ; [im Zusammenhang mit einer gleichnamigen Ausstellung vom 19. Mai bis 30. Juli 2005 in der ThULB Jena] - Wallraff, Martin (De Gruyter, 2005)
This book offers a survey of the Christian chronicle of the world: From its beginning in Late Antiquity to its heyday in the High Middle Ages, ending with its last great representatives in the age of humanism and reformation